Rasio Profitabilitas dan Penilaian Kinerja Keuangan UMKM - Laily Nurjanah; Tia Masherly Berlianna; Risxa Ayu Anggreani; Siti Mudzalifah; Tatanka Rizky Adinugroho; Hendra Dwi Prasetyo (Universitas Pendidikan Nasional, 2021)
This study analyzed the financial performance of MSME (Micro, Small and Medium Enterprises) Alove.it by using profitability ratio analysis. Methods of research using quantitative descriptive method. The type of data used for this research is secondary data. This study uses the financial statements of MSME ( Micro, Small, and Medium Enterprises) Alove.it with the period of October 2021 – November 2021. The performance can be judged as good or less good based on the results of the analysis reports on its finances. According to Harahap (2008:216), there are several financial analysis techniques that can be used to assess a company, one of them using the ratio analysis method. The technique used in this analysis is a technique of financial ratio analysis. The results showed in the month of October to November, Gross Profit Ratio decreased by 2%. However, it can still cover business expenses and also generate a net profit for the business. Overview of the months of October and November the Net Profit Margin of 42%. Overview in October and November decline in ROA by 38 % to 21 % and in October and November decline in ROE by 38% to 21%.